(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The aim of the research is to analyze the effects of the disbandment of local councils due to mafia infiltration in Liguria, Italy, through three case studies. It focuses in particular on the analysis of the political and administrative spheres of the municipalities. The research has used a qualitative approach and various sources, including documents - such as i Piani Triennali di Prevenzione della Corruzione e della Trasparenza, and interviews with key observers